Teachers as Moral Agents: The Ethics of Care and Educational Responsibility - Damayanti, Cicilia; Engliana, Engliana (Jurnal Filsafat "WISDOM", 2025)
This article examines the ethics of care through the concepts developed by prominent thinkers in the field, such as Nel Noddings and Joan Tronto. Their concepts can be effectively integrated into educational practices. The ethics of care emphasizes the significance of attending to others and our environment through concrete actions, a principle especially pertinent within educational settings. Drawing upon a comprehensive literature review of key works on the ethics of care, this study primarily utilizes Noddings' framework as its foundational analytical lens. The findings highlight that collaboration between teachers and students is crucial for cultivating a caring character. Furthermore, positive role models and support from the surrounding environment are vital in motivating individuals, thus enabling them to give positive contributions to society and the environment. This demonstrates that young learners, including those with special needs, can make significant  positive contributions to society and the environment. In conclusion, education rooted in the ethics of care not only supports students' moral development but also lays the groundwork for fostering a more empathetic and socially responsible generation.